A comparison between the Major Trauma Centre management of complex open lower limb fractures in children and the elderly. Issue 7 (July 2019) - Khadim, Muhammad Faheem; Emam, Ahmed; Wright, Thomas C.; Chapman, Thomas W.L.; Khan, Umraz
Highlights: High-energy open fractures in children or the elderly commonly required external fixation or internal fixation respectively, and free flaps. Only low-energy open fractures in the elderly were commonly considered suitable for loco-regional flaps (and internal fixation). Best outcomes depend on developing an orthoplastic infrastructure at the Major Trauma Centre and trauma pathways within the trauma network. Abstract: Introduction: Open lower limb fractures can be devastating with outcomes determined by tissue damage and adherence to strictly defined care pathways. Managing such injuries in paediatric and elderly populations presents logistical and technical challenges to achieve best outcomes. Orthoplastic principles were developed mainly in the young adult population whereas requirements for paediatric and elderly patients need further understanding. Methods: A retrospective analysis was performed on two groups of patients at the extremes of age, with type IIIb (severe) open lower limb fractures, presenting to a Major Trauma Centre (MTC) with orthoplastic services over a six-year period - the first group being under 16 years; the second group being over 65. The timelines of combined surgery to both fix the fracture and flap the soft-tissue defect were strictly observed. Each group were followed-up for a minimum of nine months. Data were analysed according to patient demographics, mechanism of trauma, time to wound excision, time to definitive surgery, fixation technique, soft-tissue reconstruction type, deep infection rate, flap survival, bony union, secondary amputation and functional outcome (Enneking score). Results: 33 paediatric patients and 99 elderly patients were identified. Paediatric: The median age was 12 years. All the children were ASA Grade I. Open tibial fractures were most common (76%) followed by ankle fracture dislocation (12%). The majority were high-energy injuries and were commonly managed with external fixators (or frames) and free flap coverage. Median hospital stay was 12 days, and time to union 114 days, with median Enneking scores of 85%. There was one flap failure and no deep infections. Elderly: The median age was 76 years. ASA grades varied and reflected multiple comorbidities. High-energy injuries required free flaps, while more common, low-energy fragility fractures were covered with loco-regional flaps. Internal fixation with intramedullary nails was most commonly used. Median hospital stay was 13 days, and time to union was 150 days, with median Enneking scores of 70%. There was one flap failure, one deep infection, and one delayed amputation. Discussion: These results reflect both similarities and important differences in managing open fractures in the extremes of age. The specific challenges of each group of patients are discussed, including surgical aspects, but also the importance of orthoplastics infrastructure within the MTC and input from allied professionals to facilitate patient pathways.